The Monitoring of Mine Atmospheres in U.K. Collieries (The Australasian Institute of Mining and Metallurgy, 1981)
The paper describes the progress made in the last decade with the introduction of comprehensive monitoring of the mine atmosphere into U.K. collieries. Brief descriptions are given of the various portable and fixed point instruments which have been developed for this purpose and the methods available for transmission of information to the surface are also discussed. The paper also outlines some of the research work being carried out both in the laboratory and underground on the development of alternative methods of fire detection. Some of the results from this work are illustrated and discussed.